GRPR versus PSMA: expression profiles during prostate cancer progression demonstrate the added value of GRPR-targeting theranostic approaches - Verhoeven, Marjolein; Ruigrok, Eline A. M.; van Leenders, Geert J. L. H.; van den Brink, Lilian; Balcioglu, Hayri E.; van Weerden, Wytske M.; Dalm, Simone U. (Frontiers in Oncology, 2023)
Central to targeted radionuclide imaging and therapy of prostate cancer (PCa) are prostate-specific membrane antigen (PSMA)-targeting radiopharmaceuticals. Gastrin-releasing peptide receptor (GRPR) targeting has been proposed as a potential additional approach for PCa theranostics. The aim of this study was to investigate to what extent and at what stage of the disease GRPR-targeting applications can complement PSMA-targeting theranostics in the management of PCa. Methods Binding of the GRPR-and PSMA-targeting radiopharmaceuticals [ 177 Lu]Lu-NeoB and [ 177 Lu]Lu-PSMA-617, respectively, was evaluated and compared on tissue sections of 20 benign prostatic hyperplasia (BPH), 16 primary PCa and 17 progressive castration-resistant PCa (CRPC) fresh frozen tissue specimens. Hematoxylin-eosin and alpha-methylacyl-CoA racemase stains were performed to identify regions of prostatic adenocarcinoma and potentially high-grade prostatic intraepithelial neoplasia. For a subset of primary PCa samples, RNA in situ hybridization (ISH) was used to identify target mRNA expression in defined tumor regions. Results The highest median [ 177 Lu]Lu-NeoB binding was observed in primary PCa samples, while median and overall [ 177 Lu]Lu-PSMA-617 binding was highest in CRPC samples. The highest [ 177 Lu]Lu-NeoB binding was observed in 3/17 CRPC samples of which one sample showed no [ 177 Lu]Lu-PSMA-617 binding. RNA ISH analyses showed a trend between mRNA expression and radiopharmaceutical binding, and confirmed the distinct GRPR and PSMA expression patterns in primary PCa observed with radiopharmaceutical Verwijderd: Marion de Jong 1 ‡ , 34 Verwijderd: ‡ In memoriam ¶ binding. Conclusion Our study emphasizes that GRPR-targeting approaches can contribute to and complement currently applied PSMA-targeting strategies in both early and late stage PCa.